A Qualitative Study of Paramedic Duty to Treat During Disaster Response. (10th April 2018) - Smith, Erin; Burkle, Frederick; Gebbie, Kristine; Ford, David; Bensimon, Cécile
Abstract: Objectives: Disasters place unprecedented demands on emergency medical services and can test paramedics personal commitment as health care professionals. Despite this challenge, guidelines and codes of ethics are largely silent on the issue, providing little to no guidance on what is expected of paramedics or how they ought to approach their duty to treat in the face of risk. The objective of this research is to explore how paramedics view their duty to treat during disasters. Methods: The authors employed qualitative methods to gather Australian paramedic perspectives. Results: Our findings suggest that paramedic decisions around duty to treat will largely depend on individual perception of risk and competing obligations. A code of ethics for paramedics would be useful, but ultimately each paramedic will interpret these suggested guidelines based on individual values and the situational context. Conclusions: Coming to an understanding of the legal issues involved and the ethical-social expectations in advance of a disaster may assist paramedics to respond willingly and appropriately. ( Disaster Med Public Health Preparedness . 2019;13:191–196)